Jumlah Uang Beredar di Indonesia (Periode 2011Q1 – 2019Q4) - Dewi Anggraini; Dewi Rahayu (PPJP Universitas Lambung Mangkurat, 2022)
It is prominent to note that supply for money has become the most saturated literature amongst researchers. Therefore, our study is designed to investigate the money supply in Indonesia.We use five variables in our models: real GDP as a proxy of output, 3-month interbank interest rate, exchange rate, and two measures of money supply: narrow money (M1) and broad money (M2). We compile our data from Indonesia's economic and financial statistics, published by Bank Indonesia, and incorporate quarterly data, encompassing the 2011:1 to 2019:4 period of time. The multiple linear regression method is deployed to assess the effect of real GDP, interest rate, and exchange rate on M1 and M2 money supply. The estimation is executed separately following two proxies of the money supply.Our results imply that real GDP and exchange rate positively affect both M1 and M2 Money supply, while interest rate generates a negative effect. These results consider that Keynes's liquidity preferences theory is suitable to examine the money supply behavior of Indonesia, in addition to the exchange rate